Developmental Dimensions in Preterm Infants During the 1st Year of Life: The Influence of Severity of Prematurity and Maternal Generalized Anxiety - Neri, Erica; Genova, Federica; Monti, Fiorella; Trombini, Elena; Biasini, Augusto; Stella, Marcello; Agostini, Francesca (Frontiers in Psychology, 2020)
Background The literature has recognized premature birth as a risk factor for infant development and maternal anxiety. This study investigated the impact of the severity of birth weight, as well as of maternal anxiety at 3 months of infants’ corrected age, on infants’ outcomes during the 1st year postpartum. Moreover, it described the longitudinal trajectories of developmental outcomes, additionally exploring the impact of anxiety. Methods The study compared 147 mothers and their 147 newborns, differentiated in 25 Extremely Low Birth Weight (ELBW), 41 Very Low Birth Weight (VLBW), and 81 Full-Term (FT) infants. At 3, 9, and 12 months (corrected age in the case of preterm infants) the level of infants’ development was investigated according to the 5 quotients (Locomotor, Personal and Social, Hearing and Language, Eye-hand Co-ordination and Performance) of the Griffiths Mental Development Scales (GMDS-R). During the assessment of 3 months, mothers fulfilled Penn State Worry Questionnaire (PSWQ) to evaluate the presence of generalized anxiety. Results Among the 5 GMDS-R quotients, significant effect of severity of birth weight emerged only for Performance quotient: preterm infants (ELBW at 3 months; VLBW at 12 months) showed lower scores than FT ones. Moreover, this quotient decreased from 3 to 9 and to 12 months for VLBW and FT infants, while it was stable for ELBW ones. A significant interaction between severity of birth weight and maternal anxiety emerged for Hearing and Language and Locomotor quotients. In the first case, scores for ELBW infants, independently from maternal anxiety, decreased from 9 to 12 months. The same results emerged for VLBW infants, in the case of non-anxious mothers. Regarding Locomotor quotient, mean scores decreased from 3 to 9 and to 12 months for all groups in the case of non-anxious mothers. Conversely, when mothers were anxious, this decrease emerged only for VLBW infants. Lastly, ELBW, VLBW and FT showed difference in the growth and slope of the trajectories of different quotients. Conclusion The severity of birth weight for preterm infants, also in interaction with maternal anxiety, had significant and specific impact on different dimensions of infants’ development. Clinical implications of these results underline the need for individualized interventions.